Assessing photosynthesis in plant systems: A cornerstone to aid in the selection of resistant and productive crops - Calzadilla, P. I.; Carvalho, F. E.L.; Gomez, R.; Lima Neto, M. C. [UNESP]; Signorelli, S. (Elsevier, 2022)
Photosynthesis is an essential metabolic pathway for plants, contributing to growth and biomass production. Environmental adverse conditions have a negative impact on photosynthetic activity, reducing crop yield and productivity, a situation that has been worsen due to the actual global climate change scenario. Plants have different mechanisms to cope with this changing environment, ranging from photo-protective mechanisms to adaptive processes aiming acclimation. To understand these processes, and in the search for resistant varieties of crops, plant scientists have been assessing photosynthetic activity under different conditions and in different plant species. There are multiple methodologies to study photosynthesis; however, not all of them are suitable for every working condition or plant species. In this review, we offer an overview of the available methodologies to assess photosynthesis, from the most conventional to other less well known. We highlight the strength and weakness of each technique, and discuss how photosynthetic measurements can be linked and integrated to other methodologies (e.g. omics). Moreover, we address how photosynthesis is affected by intra-plant and inter-plants factors, as well as environmental variables. The analysis of the photosynthetic process from a wider and systemic perspective will lead to a closer understanding of plant physiology, ultimately improving crop yield and land use efficiency.
Keywords: Abiotic stress; Chlorophyll a fluorescence; Crop yield; Gas exchange; Sustainable agriculture